Effect Of Service Quality On Customer Satisfaction At PT. BPR Kencana Sumedang - Solihin Royani (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
This research is motivated by low customer satisfaction and the purpose of this study is to determine the effect of service quality on customer satisfaction at PT. BPR Kencana Sumedang. The sampling technique used in this study was simple random sampling, namely taking members of the population randomly without regard to strata in the population. The number of samples in this study used the slovin formula, after calculating the resulting number of 97 respondents. For testing in this study used validity test, reliability test, normality test, simple regression analysis, linearity test, correlation coefficient analysis, determination analysis and T test. The results of the discussion of service quality are 4103 said (agree) as a whole which is assessed based on the score resultts indicators - indicators of 84,59% or category (Very good). Customer satisfaction with a value of 4152 is said (agree) as a whole which is assessed based on the indicators of 85,60% or the category of satisfaction and the magnitude of the influence of service quality on customer satisfaction at PT. BPR Kencana Sumedang of 34,9% and the remaining 65,1% for other factors that influence variables outside the study. The results of the hypothesis can be counclude that t count > t table is 7.140 > 1.661. This means Ho is rejected Ha is accepted, then service quality has a significant at PT.BPR Kencana Sumedang.